Analisis Strategi Penguatan Profil Pelajar Pancasila melalui Pembelajaran Berdiferensiasi dan Kompetensi Sosial Emosional SDN Gadjahmungkur 04 - Agustina, Naila Intan Muna; Mudzanatun, Mudzanatun; Patonah, Siti (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2023)
This study aims to determine the strategy in strengthening the profile of Pancasila students carried out by teachers. This research was conducted at SDN Gadjahmungkur 04 Semarang. The type of research used is narrative qualitative research. The research subjects were class 2 homeroom teachers and grade 2 students consisting of 5 students. Data collection techniques are observation, interviews and documentation. Based on the results of observations and researchers found an event carried out by the teacher in strengthening the Pancasila Student Profile through differentiation learning, project-based learning and habituation. Based on the results of research conducted by researchers, it can be seen that teachers have a good strategy in strengthening the Pancasila student profile for students. This is evidenced by the existence of subject value data, interview results, observation results and documentation of student activities. Strengthening the Pancasila student profile through differentiation learning and social-emotional competence can be carried out well by teachers. The success of strengthening the profile of Pancasila students for students requires a strategy that is carried out by the teacher carefully. Apart from the role of the teacher and family, the social environment also plays a role in strengthening the profile of Pancasila students.